RESPONSE POMEGRANATE(PUNICA GRANATUM CT. SALAKHAN) CUTTING OF FOLIAR SPRAYING WITH ALGA 600 AND GROWTH MEDIA - SALIH , ZANIAR J.; SAEED, GULALA M. A.; SHARIF, SAZAN F.; ALI , ARI J. (Journal of Duhok University, 2023)
This experiment was conducted during the growing season (2021) in Bakrajo Nursery Station/ Sulaimani, Kurdistan Region-Iraq. Uniform and healthy pomegranate (Punica granatum L..) cv. Salakhani cutting was used. Cutting pomegranate were planted in polyethylene black plastic pots each one of the with apromixlity (1L) volume, filled with different growth media to investigate the effect of three seaweed extract (Alga600) concentrations (0,2 and 4 mg. L-1) and three different growth media (Sand, Peat Moss and Mix), and their interactions on the rooting and shooting system characters of Pomegranate cv. Salakhani cutting. The results are summerized as follows: growth media significantly increase all shooting and rooting system characters. Peatmoss media is significantly superior to overall Mix and sand media except for chlorophyll and fresh leave weight parameters. The foliar spray with Alga 600 concentrations was non-significantly different in the most studied parameters except for shoot numbers. The interaction between foliar spray Alga 600 and Peatmoss as growth media was recorded as a significant difference in some parameters such as leaf area, number of shoots, number of leaves, number of roots and root length